What economists know about open source software its basic principles and research results - Sebastian von Engelhardt (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2011)
For a decade, economists have been fascinated by the phenomenon of open source software (OSS). OSS is marked by free access to the software and its source code. It is developed in a public, collaborative manner by thousands of non-paid volunteers as well as profit seeking firms. Today, OSS is well established in the ICT sector and represents a new intellectual property paradigm. This paper provides an introduction into the topic OSS versus closed source software (CSS, also called proprietary software). After a brief history of OSS and CSS, the differences between the open and the closed source principles and the basic logic of OSS business models are explained. Next, the paper presents what economists know about the OSS phenomena, i.e. gives an overview of the motives of the (non-paid) OSS developers, the institutions of OSS, the effects of OSS on competition, the incentives and role of firms, and finally of open source principle beyond software.
Keywords: L17; O34; L86; 330; open source; open source software; intellectual property rights; information and communications technologies; Open Source; Immaterialgüterrechte; Informationstechnik